Agent-based modeling of the energy network for hybrid cars. (1st July 2015) - Gonzalez de Durana, José María; Barambones, Oscar; Kremers, Enrique; Varga, Liz
Highlights: An approach to represent and calculate multicarrier energy networks has been developed. It provides a modeling method based on agents, for multicarrier energy networks. It allows the system representation on a single sheet. Energy flows circulating in the system can be observed dynamically during simulation. The method is technology independent. Abstract: Studies in complex energy networks devoted to the modeling of electrical power grids, were extended in previous work, where a computational multi-layered ontology, implemented using agent-based methods, was adopted. This structure is compatible with recently introduced Multiplex Networks which using Multi-linear Algebra generalize some of classical results for single-layer networks, to multilayer networks in steady state. Static results do not assist overly in understanding dynamic networks in which the values of the variables in the nodes and edges can change suddenly, driven by events, and even where new nodes or edges may appear or disappear, also because of other events. To address this gap, a computational agent-based model is developed to extend the multi-layer and multiplex approaches. In order to demonstrate the benefits of a dynamical extension, a model of the energy network in a hybrid car is presented as a case study.